2019
DOI: 10.1002/ptr.6390
|View full text |Cite|
|
Sign up to set email alerts
|

The mechanism of mulberry leaves against renal tubular interstitial fibrosis through ERK1/2 signaling pathway was predicted by network pharmacology and validated in human tubular epithelial cells

Abstract: Mulberry leaf was reported that it has antidiabetic activity, although the mechanisms underlying the function have not been fully elucidated. In the present study, the results of network pharmacology suggested that mulberry leaves could regulate key biological process in development of diabetes, and the process implicates multiple signaling pathways, such as JAK-STAT, MAPK, VEGF, PPAR, and Wnt. Then, the research in vitro indicated that mulberry leaves remarkably ameliorated high glucose-induced epithelial to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…All our results indicated that the miR-199a-5p-ZEB1 axis was a downstream target of LUCAT1 and that miR-199a-5p overexpression inhibited the EMT of HG-treated HK-2 cells. ZEB1 is one of the key transcription factors of EMT and plays an important role in promoting the occurrence of this process [25]. Therefore, it is reasonable to hypothesize that LUCAT1 promotes HG-induced EMT through ZEB1 by sponging miR-199a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…All our results indicated that the miR-199a-5p-ZEB1 axis was a downstream target of LUCAT1 and that miR-199a-5p overexpression inhibited the EMT of HG-treated HK-2 cells. ZEB1 is one of the key transcription factors of EMT and plays an important role in promoting the occurrence of this process [25]. Therefore, it is reasonable to hypothesize that LUCAT1 promotes HG-induced EMT through ZEB1 by sponging miR-199a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…5 Due to the complexities of compound in traditional Chinese medicine, the pathologic process of diabetes can be interfered through the interaction of various mechanisms, which could avoid further damage caused by overuse or underuse of a single target. 22,23 Therefore, YNJ could reduce podocytes injury through multiple signally pathway to avoid high autophagy beyond basal autophagy levels in podocytes exposed to high glucose.…”
Section: Discussionmentioning
confidence: 99%
“…The nodes in the network represented medicinal materials, components, targets and pathways, whereas the edges represented medicinal material–component, component–target, and target–pathway interactions. 4143…”
Section: Methodsmentioning
confidence: 99%